Avaliaçăo de sinais precoces em transtornos do espectro autista, por meio da observação de vídeos - Breistchwerdt, Jael Cristina Barros (2010)
The aim of this study was to evaluate early signs of Autism Spectrum Disorders, using retrospective video analysis. The participants were eight children later diagnosed with ASD and eight children with typical development. Home videos of the participants were collected from families, at the ages 12, 24 and 36 months. Videos were edited and then analysed by two ASD specialists. The behaviors: Eye Contact; Facial Expression; Play behavior/ Imitation; Communication; Joint Attention and Repetitive Behaviors, were analysed. The results suggest that early signs such as, deficits in Communication, Play behavior, Imitation and Repetitive behaviors, can be detected in infants at 24 months. Most importantly, findings indicate that deficit in Joint Attention was the most discriminating sign of children with ASD, as early as 12 months.